Ultrathin two-dimensional conjugated metal–organic framework single-crystalline nanosheets enabled by surfactant-assisted synthesis. Issue 29 (29th April 2020) - Wang, Zhiyong; Wang, Gang; Qi, Haoyuan; Wang, Mao; Wang, Mingchao; Park, SangWook; Wang, Huaping; Yu, Minghao; Kaiser, Ute; Fery, Andreas; Zhou, Shengqiang; Dong, Renhao; et al.
Abstract : Ultrathin and large-sized 2D conjugated MOF single-crystalline nanosheets are synthesized, which allow fast ion diffusion and high utilization of active sites, and therefore exhibit remarkable performance for Li-ion batteries. Abstract : Two-dimensional conjugated metal–organic frameworks (2D c-MOFs) have recently emerged for potential applications in (opto-)electronics, chemiresistive sensing, and energy storage and conversion, due to their excellent electrical conductivity, abundant active sites, and intrinsic porous structures. However, developing ultrathin 2D c-MOF nanosheets (NSs) for facile solution processing and integration into devices remains a great challenge, mostly due to unscalable synthesis, low yield, limited lateral size and low crystallinity. Here, we report a surfactant-assisted solution synthesis toward ultrathin 2D c-MOF NSs, including HHB-Cu (HHB = hexahydroxybenzene), HHB-Ni and HHTP-Cu (HHTP = 2, 3, 6, 7, 10, 11-hexahydroxytriphenylene). For the first time, we achieve single-crystalline HHB-Cu(Ni) NSs featured with a thickness of 4–5 nm (∼8–10 layers) and a lateral size of 0.25–0.65 μm 2, as well as single-crystalline HHTP-Cu NSs with a thickness of ∼5.1 ± 2.6 nm (∼10 layers) and a lateral size of 0.002–0.02 μm 2 . Benefiting from the ultrathin feature, the synthetic NSs allow fast ion diffusion and high utilization of active sites. As a proof of concept, when serving as a cathode material for Li-ion storage, HHB-Cu NSs deliver a remarkable rate capability (charge within 3 min) and long-term cycling stability (90% capacity retention after 1000 cycles), superior to the corresponding bulk materials and other reported MOF cathodes.